TINJAUAN HUKUM PEMIDANAAN TERHADAP PELAKU PENYALAHGUNA NARKOTIKA DENGAN SISTEM REHABILITASI - Andri Winjaya Laksana (Jurnal Pembaharuan Hukum, 2015)
Narcotics abuse has long been a serious problem in many countries. The conviction of narcotics abusers with imprisonment is an illegal law enforcement, narcotics abusers can be regardedas sick and very unwise when people mix up sick people with other offenders. The approach method used in this research is sociological juridical or socio legal research approach, that isthe way or procedure used to solve the research problem by examining secondary data in the form of legal materials or applicable law regulations then followed by conducting research on data Primary in the field. The result of the research shows that 1) The basis of criminalization of narcotics abuse with rehabilitation system is done with the classification of the Defendant when arrested in the condition of hand caught, 1 (one) day evidence was found with the detail of Law No. 35 of 2009, it was stated positive using narcotics based on Laboratory test letter based on the request of the investigator, Need Certificate from the doctor / soul psychiatrist government appointed by the judge, There is no evidence that the concerned involved in illicit narcotics. 2) The Obstacle of Criminalization Against Narcotics Abuse Culprit with Rehabilitation System due to the conflict between Laws and Regulations on the provision of rehabilitation then becomes the initial trigger for the implementation of rehabilitation in Indonesian punishment system.